Prognostic Significance of ANGPTL4 in Lung Adenocarcinoma: A Meta-Analysis Based on Integrated TCGA and GEO Databases. (7th October 2022) - Yang, Yang; Liu, Yufei; Gao, Peiyang; Liu, Ke; Zhao, Keni; Ying, Rongtao; Jiang, Jun; Xie, Xiaohong; Xiao, Wei; Huang, Qingsong; Wu, Jianying; Zhang, Chuantao
Abstract : Lung adenocarcinoma (LUAD) is a common malignant tumor with a poor prognosis. Recent studies have found that angiopoietin-like 4 (ANGPTL4) is abnormally expressed in many tumors, so it can serve as a potential prognostic marker and therapeutic target. However, its prognostic value in LUAD remains unclear. We downloaded RNA sequence data for LUAD from The Cancer Genome Atlas (TCGA) database, methylation data from the University of California Santa Cruz genome database, and clinical information. R software (version 4.1.1) was applied to analyze the ANGPTL4 expression in LUAD and nontumor samples, and the correlation with clinical characteristics to assess its prognostic and diagnostic value. In addition, we analyzed the relationship between the ANGPTL4 expression and methylation levels. Tumor IMmune Estimation Resource (TIMER) tool was taken for immune infiltration analysis, and two Gene Expression Omnibus (GEO) datasets were combined for meta-analysis. Finally, differentially expressed genes (DEGs) related to ANGPTL4 were analyzed to clarify its function. As shown in our results, ANGPTL4 was upregulated in LUAD and was an independent risk factor for the diagnosis and prognosis of LUAD. The general methylation level and eight ANGPTL4 methylation sites were significantly negatively correlated with the ANGPTL4 expression. Furthermore, we found that B cell infiltration was negatively correlated with ANGPTL4 expression and was an independent risk factor. Meta-analysis showed that the high expression of ANGPTL4 was closely associated with a poor prognosis. 153 DEGs, including the matrix metalloproteinase family, the chemokines subfamily, and the collagen family, were correlated with ANGPTL4. In this study, we found that ANGPTL4 was significantly elevated in LUAD and was closely associated with the development and poor prognosis of LUAD, suggesting that ANGPTL4 may be a prognostic biomarker and a potential therapeutic target for LUAD.